POTENSI MEDIA CAIR BERBAHAN ORGANIK SEBAGAI MEDIA ALTERNATIF UNTUK PERTUMBUHAN BAKTERI SEBAGAI PUPUK HAYATI - Asi Yanetri; Djaya A. A.; Handayani N; Neneng L. (AgriPeat, 2016)
Studies to evaluating various organic materials to propagation of bacteria as biofertilizer is still a few and research to obtain a alternative media for growing bacteria from organic materials are cheaper have been carried out in the laboratory Department of Agriculture, Faculty of Agriculture, University of Palangkaraya since September 2014 to July 2015. This study was conducted in three series of studies, such as at the first experiment knowing the growth of soil bacteria on the type of media nutrient broth (NB), coconut water, mung bean sprouts wastewater, tofu wastewater, rice washing water, boiled fish bones and boiled chicken bones up to 5 days after inoculation (dai), a second series knowing the growth of bacteria Burkholderia nodosa G5.2rif1 up to 14 dai in NB media, boiled shrimp shells, boiled snails meat and boiled catfish belly, a third series was to determine the growth of B. nodosa G5.2rif1 on media media NB, potato dextrose liquid, coconut water, tofu wastewater, and coconut oil. The conclusion is medium coconut water, mung bean sprouts waswater, tofu wastewater, rice washing water, boiled fish bones, boiled chicken bones, boiled shrimp shell, boiled a snails meat, boiled catfish belly, and potato dextrose liquid is able to increase the growth of bacteria higher compared than commercial media, as a alternative media substitute cheaper than commercial nutrient broth. Media alternatives that faster growth for soil bacteria is wastewater of mung bean sprouts and rice washing water while good media for faster promote growth of B. nodosa G5.2rif1 is boiled catfish belly, boiled snail meat, potato dextrose liquid, coconut water and tofu wastewater